Case report: Primary sarcoma of the mandible with a novel SLMAP-BRAF fusion - Zhou, Peng; Liu, Wei; Zheng, Jiaoyun; Zhang, Haixia; Luo, Jiadi (Frontiers in Oncology, 2024)
Primary sarcomas of the jaw are very rare tumor with unclear mechanism of tumorigenesis. Identification of genetic alterations contributes to better understanding of tumorigenesis and extension of tumor spectrum, as well as potential therapeutic targets application.Herein, we firstly report a case of primary sarcoma in the mandible with novel SLMAP-BRAF fusion. Morphologically, the tumor was composed of histiocyte-like cells, larger epithelioid cells, spindle cells and osteoclast-like giant cells with moderate atypia. Focally, it mimicked tenosynovial giant cell tumor or biphasic synovial sarcoma, and even giant cell tumor of bone.SATB2 was diffusely expressed, while p63 and p16 were locally positive with loss expression of p16 in histiocyte-like and larger epithelioid cells. SLMAP-BRAF (S11:B10) fusion was detected by both DNA and RNA NGS, and further verified by sanger sequencing, DNA electrophoresis and FISH. Then a descriptive diagnosis of BRAF rearrangement sarcoma with moderate-grade malignancy (non-specific type) was given according to the biological behavior, morphological features and gene alteration. The patient finished six cycles of chemotherapy after hemimaxillectomy. Within 7 months of follow-up, no tumor recurrence or metastasis was observed.Our case has enriched the spectrum of jaw bone tumor and BRAF rearrangement tumor.